UTILIZATION OF POLYCLONAL ANTIBODIES PRODUCED IN LOCAL HORSES (EQUUS CABALLUS) AS A RESOURCE FOR DEVELOPMENT OF ELISA CONJUGATE TO DETECT HEPATITIS B VIRUS (HBV) SURFACE ANTIGENS - Depamede, S.N.; Sriasih, M.; Yulianti, E. (Diponegoro University, 2012)
The aim of this study was to utilize the antibody produced using Indonesia local horses (Equuscaballus) to make the conjugate of ELISA kit for detection of hepatitis B virus (HBV) surface antigen(HBsAg). The polyclonal antibodies were isolated and purified from local horses immunized repeatedlyusing isolated and purified HBsAg from Indonesia. The antibodies were conjugated with horseradishperoxidase by a modified method of Nakane and Kawaoi. The conjugate activities were performed usingthe principle of ELISA test conducted by the researchers as well as by independent laboratory.Commercial conjugate for HBsAg ELISA was used as a comparison study. The results of this studyindicated that the antibody produced from local horses can be used to make conjugates that werecomparable to commercial HBsAg ELISA kit.